2012
DOI: 10.32398/cjhp.v10isi-latino.1480
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles Faced by Latina Mothers of Children with Autism

Abstract: The CDC's most recent autism prevalence estimates document the continued trend of higher prevalence among non-Hispanic white children compared to Hispanic children. The disproportionate underrepresentation of Latino children in the health, education and service systems is measurable, disadvantaging the child and family. This quantitative study identifies support needs and obstacles experienced by 96 Latina mothers of children with autism, active in Spanish-language parent groups in California. Study measures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…With respect to community knowledge, research has shown that Latino families and communities have limited knowledge about evidenced‐based services and how to access them (Iland et al . ; Magaña et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to community knowledge, research has shown that Latino families and communities have limited knowledge about evidenced‐based services and how to access them (Iland et al . ; Magaña et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Related to the first category, community knowledge and perception of ASD, a lack of information in the community was an important factor that creates a barrier to service use, and this factor was also identified as salient in other studies of Latino families of children with ASD (Iland et al . ; Magaña et al . ).…”
mentioning
confidence: 99%
“…8,17,19 However, parents of typically-developing children may also offer important insights into family and community factors affecting ASD diagnostic delay. Usually, a parent is not aware that his/her child has ASD until the child is at least 2-3 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Latino children are more likely to be diagnosed later and are less likely than White children to receive specialty autism services including Applied Behavioral Analysis (ABA)‐based interventions (Liptak et al., ; Magaña, Lopez, Aguinaga, & Morton, ; Mandell et al., ; Palmer, Walker, Mandell, Bayles, & Miller, ). Furthermore, a needs assessment found that the majority of Latino families surveyed needed more information about autism and helping their child, more formal and informal social support, and more financial support (Iland, Weiner, & Murawski, ). Therefore, there is a growing need for the development of effective, affordable, and culturally appropriate interventions for Latino children with ASD and their families.…”
mentioning
confidence: 99%
“…majority of Latino families surveyed needed more information about autism and helping their child, more formal and informal social support, and more financial support (Iland, Weiner, & Murawski, 2012). Therefore, there is a growing need for the development of effective, affordable, and culturally appropriate interventions for Latino children with ASD and their families.…”
mentioning
confidence: 99%